The Influence of Digital Marketing and Brand Awareness on MSME Product Sales in Sumbawa Regency - Rhea Bornily Pragass; Diah Anggeraini Hasri (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the influence of Digital Marketing and Brand Awareness on the Sales of Micro, Small, and Medium Enterprises (MSMEs) products in Sumbawa Regency. Facing challenges of intense market competition and limited access, MSMEs require effective strategies to improve sales performance. This research employed a quantitative approach by distributing questionnaires to 100 MSME owners selected using the Slovin formula sampling technique. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The analysis results indicate that the Digital Marketing (X1) and Brand Awareness (X2) variables simultaneously have a significant effect on the Sales (Y) variable, with an R-Square value of 0.718. Hypothesis testing proved that Digital Marketing (T-statistic 4.982) and Brand Awareness (T-statistic 5.733) each have a positive and significant influence on Sales. These findings confirm that implementing effective digital marketing strategies and building strong brand awareness are crucial factors for driving the sales growth of MSMEs in the local market.